Can polish university female students swim? - Robert Podstawski; Sandra Boraczynska; Krystyna Skibniewska; Ewelina Kolankowska (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Background and aim of the work: There are only few studies in Polish and foreign literature providing solid information on swimming skills of university students. The aim of the study carried out at the University of Warmia & Mazury in Olsztyn was to determine swimming skills of Polish university female students starting their studies. Material and methods: The study was conducted in 2012 on 298 female students of the 1 st year course, at the age of 19 - 20. Anonymous questionnaire was used in the research. Results: It has been shown that almost 72% of the women could not swim at all, and 26% swam poorly. Within the group of women able to swim, the greatest percentage was set by women using classical style (49%) and their own one (27%) and only 13% of the students used crawl, 9% - back stroke and 2% - butterfly style. Of all the women declaring swimming abilities, the biggest percentage (16%) could cover the distance of only 20 - 50 m; fewer students (6%) covered the distance of 50 - 100 m; and 5% could swim only 20 m. Only a marginal number of students (2%) could cover the distance from 100 to 1000 m; none could swim more than 1000 m. Conclusions: The study showed a very pessimistic picture of swimming skills of Polish university female students in respect of the number of women able to swim, their knowledge of swimming styles, and the length of the covered distance.